Determination of p-Phenylenediamine Using Electrochemically Reduced Graphene Oxide - Wang, Chunyan; Lan, Yanfei; Liao, Binqian; Li, Dan; Zhu, Meiwu (Asian Journal of Chemistry, 2014)
In this communication, we report a green and effective approach to construct a sensitive detection platform based on electrochemically reduced graphene oxide modified electrode (EG@GCE). The surface morphology and structure of electrochemical reduction of graphene oxide were investigated by utilizing transmission electron microscope, FT-IR spectra, UV-visible spectra and X-ray diffraction. This EG@GCE exhibits sensitive current responses toward the electrooxidation of p-phenylenediamine (PDA) due to the excellent conductivity and large electroactive surface area of electrochemical reduction of graphene oxide and the strong p-p stacking interactions between p-phenylenediamine and the electrochemical reduction of graphene oxide surface. Moreover, a low detection limit of 1.08 μM (S/N = 3) with the linear range of 5 to 200 μM is obtained. This new finding demonstrates that the electrochemical reduction of graphene oxide is a promising candidate of advanced electrode materials for electrochemical determination aromatic amines in environmental analysis.